Natural Convection Between Two Nonuniformly Heated Coaxial Cylinders - Skiepko, J.; Ngoc Hien, Ha (Engineering Transactions, 1986)
The problem of natural convection between two coaxial, horizontal cylinders is investigated. One of the cylinders is nonuniformly heated. To find the parameters of the flow, an approximate method is given. It is a generalization of the Mack’s and Bishop’s method. The method can be applied for not too high Rayleigh numbers and for symmetrically distributed temperature on cylinders, with respect to the vertical plane of symmetry. Two simple cases are discussed in detail. In the first case, the distribution of temperature on the outer cylinder has the form Θ = cos ϕ (ϕ - angular coordinate) and the temperature of the inner cylinder is constant. In the second case, the temperature on the outer cylinder is given by Θ = 1 + a cos ϕ and the inner cylinder is maintained at constant temperature.